More than data repositories: perceived information needs for the development of social sciences and humanities research infrastructures - Anna Sendra; Elina Late; Sanna Kumpulainen (Information Research: An International Electronic Journal)
Introduction. The digitalization of social sciences and humanities research necessitates research infrastructures. However, this transformation is still incipient, highlighting the need to better understand how to successfully support data-intensive research.